When Pulmonary Tuberculosis Leads to Pneumothorax: An Unusual Presentation - Giesta, Catarina Bettencourt; d’Almeida, Manuel; Ferreira, Sara Pires (Brazilian Journal of Case Reports, 2024)
Spontaneous secondary pneumothorax (SSP) is a rare but serious complication of pulmonary tuberculosis (TB), often resulting from cavitary lung disease. A 38-year-old male presented with pleuritic chest pain and fever, with imaging revealing a left-sided pneumothorax and cavitary lesions. Diagnosis was confirmed via sputum analysis positive for Mycobacterium tuberculosis. The patient was treated with standard anti-TB therapy and a chest drain, leading to clinical improvement. SSP in TB occurs due to ruptured subpleural lesions, requiring prompt management of both pneumothorax and TB. Early diagnosis and integrated treatment are essential, particularly in high-prevalence settings.